2021
DOI: 10.1002/acp.3892
|View full text |Cite
|
Sign up to set email alerts
|

Structured groups make more accurate veracity judgements than individuals

Abstract: Groups often make better judgements than individuals, and recent research suggests that this phenomenon extends to the deception detection domain. The present research investigated whether the influence of groups enhances the accuracy of judgements, and whether group size influences deception detection accuracy. Two‐hundred fifty participants evaluated written statements with a pre‐established detection accuracy rate of 60% in terms of veracity before viewing either the judgements and rationales of several oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…As such, groups of people are responsible for flagging and reporting suspicious behavior. Research has shown that, on one hand, groups, especially established groups with prior interaction, can detect deception more accurately than individuals ( Klein and Epley, 2015 ; McHaney et al, 2018 ; Hamlin et al, 2021 ). On the other hand, group size does not significantly affect detection accuracy ( Hamlin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, groups of people are responsible for flagging and reporting suspicious behavior. Research has shown that, on one hand, groups, especially established groups with prior interaction, can detect deception more accurately than individuals ( Klein and Epley, 2015 ; McHaney et al, 2018 ; Hamlin et al, 2021 ). On the other hand, group size does not significantly affect detection accuracy ( Hamlin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that, on one hand, groups, especially established groups with prior interaction, can detect deception more accurately than individuals ( Klein and Epley, 2015 ; McHaney et al, 2018 ; Hamlin et al, 2021 ). On the other hand, group size does not significantly affect detection accuracy ( Hamlin et al, 2021 ). Multiple individuals may also deceive collectively [e.g., interviewing multiple suspects simultaneously in Vernham and Vrij (2015) and Vernham et al (2016) ].…”
Section: Introductionmentioning
confidence: 99%